Fenomena Fatherless di Indonesia dan Urgensi Rekonstruksi Syarat Hadanah: Tinjauan Sosiologi Hukum Islam - Nandu Riana; Yudi Wahyudin; Encum Sumirah; Samsul Bahri; Ahmad Nurjaman (LEX FAMILIA: Journal of Islamic Family Law, 2026)
The fatherless phenomenon in Indonesia has become a concerning social problem, where many children grow up without the emotional and psychological involvement of their fathers in parenting. This study aims to: first, analyze the fatherless phenomenon and its contributing factors within the context of Islamic family law; second, examine the relevance of hadanah requirements in classical fiqh and Indonesian positive law to contemporary social realities; and third, formulate a reconstruction concept of hadanah requirements based on the sociology of Islamic law. This study employs a normative legal research method with a sociology of Islamic law approach, utilizing primary and secondary legal materials analyzed qualitatively through content analysis within the framework of maqāṣid sharī'ah theory. The findings reveal that the fatherless phenomenon is caused by multidimensional factors including divorce, irresponsible fathers, and emotional absence, which correlate with long-term psychological impacts such as midlife crisis. Article 105 of the Compilation of Islamic Law proves inadequate as it only regulates physical-material aspects of custody without incorporating indicators of parental emotional involvement. The proposed reconstruction encompasses three integrative dimensions: a normative dimension adding emotional and psychological involvement requirements, an institutional dimension implementing shared parenting models, and an implementative dimension developing post-verdict monitoring mechanisms, all grounded in maqāṣid sharī'ah and maslahah principles.